Production, Characterization And Expression Of An Organic Solvent Tolerant Lipase From Pseudomonas Aeruginosa S5s5 - Baharum, Syarul Nataqain (2005)
Lipolytic bacterium was screened from five pure bacteria cultures available in Enzyme and Microbial Technology laboratory in UPM. The stock cultures were tested for lipase production. Two isolates (S5 and 205W) showed the highest activity in tripticase soy broth and brain heart infusions. These isolates were further incubated in different basal media. Isolate S5 was shown to give higher activity (0.327 Ulml) than isolate 205W in media MI and stable in various organic solvents tested. Therefore isolate S5 was chosen for further studies. Based on its morphological, biochemical characteristics and 16s rDNA sequence, strain S5 was identified as Pseudomonas aeruginosa. P. aeruginosa lipase exhibited the highest relative activity with n-hexane (410%) for 20 min reaction. Optimum lipase production was obtained at pH 7.0 and 37°C at static condition with peptone as the best nitrogen source and olive oil as the best carbon source. The best inoculum size was 6%. The surfactants, Tween 60 and Tween 80 were found to enhance for bacterial growth and lipase production by S5. The lipase was purified to homogeneity by affinity column chromatography and anion exchange column chromatography. The purified lipase was highly homogeneous as determined by sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDSPAGE) and the molecular mass was estimated to be 60 kDa by SDS-PAGE and G-100 gel filtration column chromatography. The optimum temperature and pH of the purified enzyme was 45°C and pH 9.0, respectively. S5 lipase was stable at pH 6-9 for 30 min. The half-life of the S5 lipase at 45°C and 50°C was 2 h and 1 h, respectively. The lipase exhibited high stability in the presence of n-dodecane, 1-pentanol and toluene. As for metal ions, it was found that ca2+ stimulated lipase activity in 15 min incubation time, while EDTA had no effect on lipase activity. However, the S5 lipase was strongly inhibited by the addition of 1 mM phenyl methyl sulfonyl fluoride (PMSF) (87% inhibition) and 1 rnM of Pepstatin (76% inhibition) after 30 min incubation. The S5 lipase exhibited the highest activity in the presence of palm oil as a substrate and followed by coconut oil. S5 lipase was found to have the highest activity against triolein which possess longer carbon chain length. S5 lipase is a non-specific lipase as shown by triolein hydrolysis. The gene encoding for the intracellular lipase of P. aeruginosa strain S5 was isolated via genomic DNA library and cloned into pRSET. The cloned sequence included two open reading frames (OW) consisting of 1575 bp for the first ORF (ORF1) and 582 bp for the second ORF (ORF2). The OW2 was located at the downstream and function as the act gene for O w l . The conserved pentapeptide Gly- X- Ser- X-Gly was located in the ORF1. Catalytic triad resembling of that serine protease, consisting of serine, histidine, aspartic acid or glutarnic acid residues was present in this lipase gene. Expression in E.coli resulted a 100-fold increase in enzyme activity after 9 h induction with 0.75 mM IPTG. The recombinant plasmid revealed a size of 60 kDa on SDS-PAGE. The Lip S5 gene was stable in the presence of 25% (v/v) n-dodecane and n-tetradecane after 2 h incubation at 37OC. Predicted 3D structure of S5 lipase revealed topological organization of a / @-hydrolase fold consisting of 10 a-Helices and 5 @-strands. The Ramachandran plot of S5 lipase showed that 85.8% (229) of residues lie in the most-favored region and only 2.2% (6) of residue lie in generously allowed regions and 1 residue lie in disallowed region.